Technical Note – Lateral Approach to the Lumbar Spine for the Removal of Interbody Cages - Moisi, Marc (Cureus, 2015)
Revision surgery to address the migration or fracture of a lumbar interbody cage can be technically challenging. Scar tissue and fibrosis, among other anatomic barriers, can make removal of the cage a complicated procedure, potentially increasing postoperative pain as well as the probability of neurologic deficits. Use of the lateral surgical technique for removal of the cage can avoid these potential complications. In this case report, we describe the removal of interbody cages through a lateral approach in three patients without the necessity of additional posterior hardware revision.